Micronized natural progesterone (Seidigestan®) vs GnRH antagonists for preventing the LH surge during controlled ovarian stimulation (PRO_NAT study): study protocol of a randomized clinical trial - Martínez-Moya, M.; Guerrero, J.; Girela, J. L.; Pitas, A.; Bernabeu, A.; Bernabeu, R.; Castillo, J. C. (Frontiers in Endocrinology, 2024)
Introduction Progesterone-primed cycles effectively suppress the pituitary LH surge during ovarian stimulation in oocyte donors and in the infertile population. Particularly in oocyte donors, the use of synthetic progesterone (progestins) has been explored in prospective clinical trials, showing mixed results. This trial was designed to determine whether the use of micronized natural progesterone is as effective as the GnRH-antagonist protocol in terms of the number of mature oocytes (MII) retrieved in oocyte donation cycles as a primary outcome, and it also aims to explore the corresponding results in recipients as a secondary outcome. Methods We propose a prospective, open-label, non-inferiority clinical trial to compare a novel approach for oocyte donors with a control group, which follows the standard ovarian stimulation protocol used in our institution. A total of 150 donors (75 in each group) will be recruited and randomized using a computer algorithm. After obtaining informed consent, participants will be randomly assigned to one of two ovarian stimulation protocols: either the standard GnRH antagonist or the oral micronized natural progesterone protocol. Both groups will receive recombinant gonadotropins tailored to their antral follicle count and prior donation experiences, if any. The primary outcome is the number of mature metaphase II (MII) oocytes. Secondary measures include treatment duration, pregnancy outcomes in recipients, as well as the economic cost per MII oocyte obtained in each treatment regimen. Analyses for the primary outcome will be conducted in both the intention-to-treat (ITT) and per-protocol (PP) populations. Each donor can participate only once during the recruitment period. The estimated duration of the study is six months for the primary outcome and 15 months for the secondary outcomes. Discussion The outcomes of this trial have the potential to inform evidence-based adjustments in the management of ovarian stimulation protocols for oocyte donors.